2018
DOI: 10.3758/s13415-018-0565-9
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory brain activity differentially reflects false belief understanding and complementation syntax processing

Abstract: False belief understanding (FBU) enables people to consider conflicting beliefs about the same situation. While language has been demonstrated to be a correlate of FBU, there is still controversy about the extent to which a specific aspect of language, complementation syntax, is a necessary condition for FBU. The present study tested an important notion from the debate proposing that complementation syntax task is redundant to FBU measures. Specifically, we examined electrophysiological correlates of false bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 93 publications
(134 reference statements)
4
13
1
Order By: Relevance
“…In short, the present study quantifies event-related potentials and measures of oscillatory brain activity, collected in a sample of school-age children, to characterize the neural correlates of belief and complementation tasks in this age group. Basing hypotheses on the parallel adult study (Guan et al, 2018) we expected to observe divergent macroscopic correlates for the two tasks, in support of the notion that despite their similarities, FBU and complementation syntax involve markedly different large-scale cortical processes.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…In short, the present study quantifies event-related potentials and measures of oscillatory brain activity, collected in a sample of school-age children, to characterize the neural correlates of belief and complementation tasks in this age group. Basing hypotheses on the parallel adult study (Guan et al, 2018) we expected to observe divergent macroscopic correlates for the two tasks, in support of the notion that despite their similarities, FBU and complementation syntax involve markedly different large-scale cortical processes.…”
supporting
confidence: 71%
“…While it is difficult to evaluate this redundancy hypothesis at the behavioral level, three neurophysiological studies, all with adults, have focused on the comparison between false belief and false complementation (Guan et al, 2018;Chen et al, 2012;Cheung et al, 2012). A fMRI study showed that the right temporo-parietal junction, a brain area responsible for understanding mental states (Sommer et al, 2007;Gobbini & Haxby, 2007;Bedny et al, 2009), was recruited by both false belief and false complementation (Cheung et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the involvement of all three frequency bands is consistent with earlier work, showing the complexity of the neural systems underlying this sophisticated cognitive skill ( Mossad et al , 2016 ). Previous studies using electroencephalography have shown involvement of alpha and beta oscillatory power as well as parietal–occipital regional coupling in beta band in ToM conditions compared to control conditions ( Guan et al , 2018 ). In a study of joint attention, a precursor skill to ToM, comparing typically developing children and children with autism spectrum disorder, authors found that FT children showed increased beta oscillatory power in the temporal parietal junction prior to displaying joint attention while autism spectrum disorder children did not.…”
Section: Discussionmentioning
confidence: 91%
“…The tensed complement John got her flowers may be inconsistent with reality, but the entire sentence is accurate because it conveys the belief that Mary holds even though it is an incorrect one. To test whether there is any overlap in the underlying mechanisms of these two aspects of belief understanding (with understanding of false complementation being more dependent on language), Guan et al () presented their participants with cartoon stories and used comprehension questions to probe their understanding of false and true belief and of complementation. False belief scenarios were object‐transfer scenarios (Wimmer & Perner, ) in which the location of the target object was changed while the protagonist was out of the room (the location remained the same in the true controls).…”
Section: Discourse and Pragmaticsmentioning
confidence: 99%